Unlisted : a story of schizophrenia - Ruston, Delaney; Haugse, William; Okazaki, Steven (Seattle, WA : MyDoc Productions, 2010)
A first person account of Delaney Ruston's troubled relationship with her father who suffers from Paranoid schizophrenia. After a 10 year separation, she reconnects with her father and her experiences highlights the effects of mental illness on families, and the urgent need for a better mental health care system in America.
Documentary./ Date from disc surface; date on credits c2009./ Accompanied by a discussion guide inside the DVD case./ Participants: Narrator: Delaney Ruston; Bonnie Buchanan, Michael Chambers, Jim McDermott, Mel Lewin, Eileen Miller, Richard Ruston, Sarah Steyer, Chase Small, Tessa Small, Peter Small, Tod Lipkin, Stephanie Watari, Lesley Devine.
Keywords: Schizophrenia; Paranoid schizophrenia; Mental health services